2019
DOI: 10.1105/tpc.19.00233
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Regulation of Plant Epidermal Wax Synthesis through Antagonistic Roles of the Transcription Factors SPL9 and DEWAX

Abstract: Plant surface waxes form an outer barrier that protects the plant from many forms of environmental stress. The deposition of cuticular waxes on the plant surface is regulated by external environmental changes, including light and dark cycles. However, the underlying molecular mechanisms controlling light regulation of wax production are still poorly understood, especially at the posttranscriptional level. In this paper, we report the regulation of cuticular wax production by the miR156-SPL9 (SQUAMOSA PROMOTER … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 83 publications
(141 reference statements)
0
35
0
Order By: Relevance
“…The role of miR156 in plant growth and development has been well documented [ 19 , 24 , 25 , 26 , 27 ], but functional characterization of its target SPL genes is still lagging, especially in major crops, such as alfalfa. In this study, we found MsSPL9 to play a role in determining plant height and stem thickness in alfalfa.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The role of miR156 in plant growth and development has been well documented [ 19 , 24 , 25 , 26 , 27 ], but functional characterization of its target SPL genes is still lagging, especially in major crops, such as alfalfa. In this study, we found MsSPL9 to play a role in determining plant height and stem thickness in alfalfa.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs have been garnering attention for their roles in regulating various aspects of development and stress response in plants [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Specifically, studies have shown that alfalfa yield as well as tolerance to heat, salt, and drought stress are improved or maintained in miR156 overexpression (miR156OE) plants [ 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations